Retrovirus-Like Long-Terminal Repeat DQ-LTR13 and Genetic Susceptibility to Type 1 Diabetes and Autoimmune Addison’s Disease - Gambelunghe, Giovanni; Kockum, Ingrid; Bini, Vittorio; Giorgi, Giovanni De; Celi, Federica; Betterle, Corrado; Giordano, Roberta; Libè, Rossella; Falorni, Alberto (Diabetes (New York, N.Y.), 2005)
Retrovirus-Like Long-Terminal Repeat DQ-LTR13 and Genetic Susceptibility to Type 1 Diabetes and Autoimmune Addison’s Disease Giovanni Gambelunghe 1 , Ingrid Kockum 2 , Vittorio Bini 3 , Giovanni De Giorgi 3 , Federica Celi 3 , Corrado Betterle 4 , Roberta Giordano 5 , Rossella Libè 6 , Alberto Falorni 1 and on behalf of the Umbria Type 1 Diabetes Registry and the Italian Addison Network 1 Department of Internal Medicine, University of Perugia, Perugia, Italy 2 Department of Molecular Medicine, Karolinska Institute, Stockholm, Sweden 3 Department of Gynecologic, Obstetrics and Paediatric Sciences, University of Perugia, Perugia, Italy 4 Department of Medical and Surgical Sciences, University of Padova, Padova, Italy 5 Division of Endocrinology, Department of Internal Medicine, University of Turin, Turin, Italy 6 Institute of Endocrine Sciences, University of Milan, Ospedale Maggiore IRCCS, Milan, Italy Address correspondence and reprint requests to Alberto Falorni, MD, PhD, Department of Internal Medicine, Section of Internal Medicine and Endocrine & Metabolic Sciences, University of Perugia, Via E. Dal Pozzo, I-06126 Perugia, Italy. E-mail: falorniatdimisem.med.unipg.it Abstract Controversial data are available on the association between the retrovirus-like long-terminal repeat (LTR) DQ-LTR13 and genetic susceptibility to type 1 diabetes and other autoimmune diseases. We analyzed DNA samples from 315 type 1 diabetic patients, 166 autoimmune Addison’s disease (AAD) patients, 1,054 healthy subjects, and 144 families of type 1 diabetic offspring. DQ-LTR13 was more frequent among patients than healthy subjects ( P c < 0.0006), and a preferential transmission of DQB1*0302-LTR13 + from parents to type 1 diabetic offspring was observed. DQ-LTR13 was in linkage disequilibrium (LD) with DQB1*0302 but not DQB1*0201. The presence of DQ-LTR13 increased the odds ratio of DQB1*0302 2.9- to 3.2-fold for type 1 diabetes and AAD. DRB1*0403 was absent in all of the 169 DRB1*04-positive patients but present in 27% (34 of 127) DRB1*04-positive healthy subjects ( P c < 0.001). DQ-LTR13 was detected in 1 of 34 (3%) DRB1*0403-positive healthy subjects and 36 of 93 (39%) individuals carrying another DRB1*04 allele ( P c = 0.002). Multivariate logistic regression analysis revealed that DQ-LTR13 is not independently associated with type 1 diabetes and AAD after correction for DQB1*0302 and DRB1*0403. Conversely, DQB1*0201, DQB1*0302, DRB1*0401, and DRB1*0403 were all significantly associated with disease risk also after correction for DQ-LTR13. We provide conclusive evidence that the genetic association of DQ-LTR13 with type 1 diabetes and AAD is primarily due to a LD with DQB1*0302 and DRB1*0403. AAD, autoimmune Addison’s disease LD, linkage disequilibrium LTR, long-terminal repeat Footnotes Accepted December 6, 2004. Received September 1, 2004. DIABETES